Faktor-Faktor Yang Mempengaruhi Adopsi Pembayaran QR Code (QRIS) di Toko Fisik - Jundy Kumoro, Chowal; Ryandini, Elda Yulia; Samin, Nurdin (Journal of Innovation in Management, Accounting and Business, 2024)
In the digital transformation era, Quick Response Code Standar Indonesia (QRIS) has emerged as a highly effective solution for facilitating payment transactions in Indonesia. With millions of users and a substantial increase in transaction volume, QRIS plays a crucial role in the ongoing digitization of the financial sector. The prevalent use of mobile phones, reaching 67.88%, further supports the trend of non-cash transactions through e-wallets, e-money, and mobile banking. This quantitative descriptive study with 85 QRIS users in Surabaya aims to analyze perceived usefulness, relative advantage, perceived ease of use, social influence, behavioral intention, and QRIS adoption. The findings indicate that perceived usefulness, relative advantage, perceived ease of use, and social influence significantly influence the behavioral intention to use QRIS, which subsequently leads to its adoption. Users are confident in the benefits of QRIS, perceiving it as an innovative and advantageous digital payment method compared to traditional cash payments. This confidence is reinforced by the ease of use and quick learning associated with QRIS, along with social recommendations. To enhance QRIS adoption, collaboration with new merchants, attractive incentives, and expanding domestic and international usage are recommended. Offering tangible benefits to merchants can further stimulate QRIS ecosystem growth, increase market presence, and drive usage expansion. However, the study's limitation lies in its sample size and focus on specific variables, urging caution in generalizing the findings to the entire population.